MIGRASI SUBJEK MENOLAK REZIM PARTISI DAN DISSENSUS DALAM FILM HIDDEN FIGURES - Saragih, Evi Irawanti (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2022)
Hidden Figures is a movie based on true story about the struggle of 3 (three) intelligent women from black race on very first NASA’S space program in 1961. A practice of Policy that makes black race can’t get important position in American society caused them receive discrimination. Based on consciousness that people depart from the same knowledge encourage them to do something across their positions to achieve equality. This study aims to explain what the characters on Hidden figures movie do to resist practice of policy and dissensus that has been divided by the regime partition in order to achieve equality and also to know what kind of migration they have succeeded. The data in form of pictures, monologues or dialogues will be analyzed using theory of Political and Aesthetic Equality by Jacques Ranciere. The result of discussion shows that every character does the political actions and make them in better position in American society. Although racism, discrimination cannot be eliminated through their actions, they have opened avenue and opportunity for anyone who has the ability to get what they deserve regardless of race, ethnicity, religion, even gender. They are no longer hidden figures or trying to be hidden by the regime in power.